Knowledge, attitude, and practice of medication and its influencing factors among residents in western China: a large-scale cross-sectional study - Shi, Hong-xia; Tan, Xue; Shu, Jian-qin; Zhou, Jun; Dan, Si-yuan; Yang, Lin; Chen, Ze-lian (Frontiers in Medicine, 2024)
Background This study aimed to understand the knowledge, attitude, and practice (KAP) of drug use among residents in western China and its influencing factors for accurately designing the knowledge, contents, and methods of popular science activities for safe drug use among residents to provide a reference for conducting rational drug use educational activities and improving residents’ level of safe drug use. Methods A cross-sectional questionnaire survey was conducted to investigate the KAP of medication among western China residents and its influencing factors from March to April 2023. Each question option was assigned a score according to logic, and the risk factors for resident medication safety KAP were explored through univariate and logistic regression analyses. Results A total of 7,557 valid questionnaires were collected, with an effective recovery rate of 96.7%. The average scores of KAP were 72.77 ± 22.91, 32.89 ± 10.64, and 71.27 ± 19.09, respectively. In the evaluation criteria of the questionnaire, the score of medication knowledge reached “good,” and the score of attitude and practice was “average.” Multiple linear regression analysis indicated that male sex and low education level were significant factors affecting the lack of drug knowledge among residents. Old age and low education level were the factors of poor attitude toward medication. The low condition of medical security was a factor in residents’ irregular drug use behavior. Conclusion The overall level of rational drug use among residents in western China is good, but there are still some inconsistencies. Rational drug use education should be conducted according to the risk points of residents in drug safety KAP to further improve the level of rational drug use of residents.